1994
DOI: 10.1080/00039896.1994.9934415
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption Patterns and Blood Mercury Levels in Wisconsin Chippewa Indians

Abstract: Methylmercury is a known neurotoxin at high blood levels (> 400 micrograms/l) and is thought to cause neurologic symptoms at substantially lower levels in susceptible adults and infants. Given that levels of methylmercury in fish in northern Wisconsin lakes can be high (> 1 ppm, FDA standard) and Chippewa Indians take large amounts of fish from these lakes, the extent of their exposure to methylmercury was investigated. Using tribal-maintained registries, 465 Chippewa adults living on reservation were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
20
1
1
Order By: Relevance
“…But many studies have raised concerns that fishing in contaminated waters, lower awareness of fish consumption advisories, and higher levels of fish consumption by ethnic minority groups have created potential health risks (cf. Peterson et al 1994;West et al 1992). Hutchison and Kraft (1994) found that Hmong residents of Green Bay consumed 90% of the fish they caught and that these consumption rates were above the average for this area.…”
Section: Review Of Literaturementioning
confidence: 99%
“…But many studies have raised concerns that fishing in contaminated waters, lower awareness of fish consumption advisories, and higher levels of fish consumption by ethnic minority groups have created potential health risks (cf. Peterson et al 1994;West et al 1992). Hutchison and Kraft (1994) found that Hmong residents of Green Bay consumed 90% of the fish they caught and that these consumption rates were above the average for this area.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Elevated mercury concentration has been detected in the blood and/or body tissues of fish consumers of the Great Lakes-St. Lawrence River basin (Cole et al, 2004;Mahaffey and Mergler, 1998) including the native population (Dellinger, 2004;Peterson et al, 1994;Roe, 2003). Blood mercury levels of sport-fish eaters were significantly associated with levels of fish consumption; mercury levels among fish eaters of the Areas of Concern (AOCs) have been higher than in many other Great Lakes populations (Cole et al, 2004).…”
Section: Mercury In the Great Lakesmentioning
confidence: 99%
“…Various methods have been used to assess nutrient values in children, such as the 24-h dietary recall form, food frequency questionnaire, and dietary records. This investigation employed a modified food frequency questionnaire designed specifically for this study and used questions similar to those asked by Peterson et al (1994) in a study that evaluated the fish consumption patterns and blood mercury levels of Wisconsin Chippewa Indians. The modified food frequency questionnaire was added to an already existing health screening questionnaire that either parents or caretakers of the children completed at baseline.…”
Section: Dietary Mercury Exposure By Modified Food Frequency Questionmentioning
confidence: 99%
“…It is estimated that 86% of mercury in the diet is derived from fish consumption (U.S. Department of Health and Human Services, 1994). Concentrations of methylmercury are highest in predatory fish such as pike, tuna, swordfish, walleye, and bass (Svensson et al, 1992;Cernichiari et al, 1995;Marsh et al, 1995;Peterson et al, 1994). People who consume fish frequently have increased exposure to methylmercury.…”
mentioning
confidence: 99%